Determination of air quality using index of atmospheric purity and antioxidant activity in lichens from Gunung Jerai and Sungai Petani, Kedah, Malaysia - Rosli, Nur Syuhada (2019)
Lichens are excellent bio-indicator for air quality assessment and they can be utilised as natural sources of antioxidant. Index of Atmospheric Purity (IAP) is an ecological index that uses lichen frequency to quantify environmental conditions, primarily air pollution. The IAP technique is considered new and has not been used extensively in Malaysia. Thus, the aims of the study are to: (i) determine the lichen diversity index of Gunung Jerai(GJ) and Sungai Petani (SP) using Shannon’s Index (ii) determine and compare the Index of Atmospheric Purity score of forested site; Gunung Jerai and urban site; Sg. Petani (iii) determine the antioxidant activity of selected lichens species. The lichens were collected at GJ (80 m, 300 m, 600 m, 900 m &1200 m) and SP within 5 x 10 m sampling site size. Twelve trees were chosen at each sampling site and the tree barks were marked with 10 x 50 cm sampling grid. Lichens attached at tree barks above 100 cm from the ground were collected. Standard morphological and chemical tests were conducted for lichen species identification. As for antioxidant evaluation, total phenolic content and total flavonoid content were assessed with DPPH assay. The lichen diversity index of GJ (3.8862) is higher compare to SP (1.5942). The air quality of sampling area, GJ and SP were determined by IAP score, low score indicated high level of pollution. Based on the Quality Level of IAP Table, GJ is classified as low level of pollution (IAP score of 42.12) and SP (8.3) as very highly polluted. Lichens IAP levels are predominantly affected by lichen habitat disturbance and air pollution. In SP, close proximity of the sampling to the main road traffic may contribute to be cause of the low IAP reading. Meanwhile, in GJ, recreational activities may contribute to the habitat disruption of lichens and low IAP score. For antioxidant activity, the antioxidant activity of acetone extract of Ramalina farinacea is highest among other species. The antioxidant content levels are as follow: Ramalina farinacea >Cladonia sp.>Parmelia sp.>Cladia aggregata. Overall, both GJ and SP are vulnerable to air pollution and lichen species reduction due to habitat disturbance. Effective enforcement should be taken by Department of Forestry in order to preserve the pristine conditions of GJ. Besides, the lichens potential as antioxidants source should be explored extensively in terms of application and commercialization.